Seeds cryopreservation and genetic diversity of neolamarckia cadamba (roxb.) bosser - Nurfaizah, Matra (Universiti Malaysia Sarawak (UNIMAS), 2013)
N. cadamba is considered as one of the best raw material for plywood industries and expected to become increasingly important for wood industries. The aim of seed storage for conserving woody species of N. cadamba is important to maintain the initial genetic and physiological quality of the germplasm until it is used or regenerated. The understanding of the genetic relatedness and genetic structure of forest tree species is essential for the proper utilization of forest genetic resources, especially for genetic improvement of tree plantation establishment or for management and conservation of natural resources. This study was aimed at assessing the suitability and effectiveness of dehydration and vitrification techniques in cryopreserving N. cadamba seeds. Dehydration in laminar air flow for 90 minutes gave the best result of germination percentage, 47% with 1.3% moisture content, followed by sucrose (40% germination and 1.5% moisture content) and silica gel (39.6% germination with 1.3% moisture content). However, the result was decreased in germination and did not give significant different in moisture content when compared to the control sample (71% germination and 1.75% moisture content). Thus, the dehydration techniques were discarded before the seed storage experiment. For vitrification, pre-treatment using 0.2M sucrose with PVS2 for the period of 60 minutes gave the highest germination of 60%. Vitrification technique (without dehydration) resulted in high germination percentage after cryopreserved in liquid nitrogen for three and six months, which was 70% and 62% respectively. This suggested that N. cadamba seeds can be stored in LN, and preculturing (before vitrification) is an essential step for successful cryopreservation. However, the germination percentages difference was not significantly different with the control seeds (without PVS2 treatment), which was 68% and 58% for three months and six months respectively. SSR markers analysis revealed that most of the microsatellite loci showed high polymorphism in all populations, as indicated by the number of alleles detected at particular loci and by the PIC value, which was above 0.5. The PIC value was ranging from 0.359 (NCGTG11) to 0.671 (NCAC11), and the mean gene diversity across loci was 0.594 with a range of 0.382 to 0.717, indicating high level of information of the chosen microsatellite set. Overall, the mean He across loci was approximately 0.597, while the Ho was 0.103. The value for He was highest for NCAC11 (0.719) and lowest for NCGTG11 (0.383). Cluster analysis was carried out for all the seven mother trees and their progenies (half-sib family) using UPGMA method. The analysis showed that most of the mother trees were not closely related, while most of the progenies were inherit from same maternal trees and other selected mother trees. The data indicated that the population was predominantly outcrossed. This study has provided new information on genetic diversity and relatedness of N. cadamba species using SSR marker. The selected mother trees in this study can be used as a potential seed source for breeding and tree improvement programmes.